Investigation of Flow Control for the Hypersonic Inlets via Counter Flow - Xiaoqiang Fan; Yuan Tao (International Journal of Aerospace Engineering)
Experimental results show that there exist two flow fields in the hypersonic inlets when the forebody waves interact with the lip boundary, which is similar to the shock reflection ion hysteresis phenomenon. In order to improve the performance of the flow field, counterflow is applied to control the shock reflection configuration in the hypersonic inlets. For better understanding of the internal mechanism, inviscid numerical simulation is conducted. And the results demonstrate that it is feasible to realize the transition between the regular reflection configuration and the Mach reflection ion configuration in the hypersonic inlets. That is because the von Neumann criterion and detached criterion play a dominant role, respectively, in these transitions. In addition, the evolution process of Mach reflection ion in the hypersonic inlets can be divided into three stages: transmission of waves, emergence of Mach stem, and stabilization of flow field.